A comparative study of the effects of phase composition on optical properties and photocatalytic activity of α-/β-/γ-Bi2O3 multi-heterojunction prepared by submerged DC electrical arc discharge. (15th October 2022) - Hashemi, E.; Poursalehi, R.; Delavari, H.
ABSTRACT: α-/β-/γ-Bi2 O3 photocatalytic nanocomposite was prepared through thermal treatment of synthesised nanoparticles by submerged arc discharge . FE-SEM reveals the formation of flake nanostructures after thermal treatment. The signatures of multi-heterojunction formation among α-, β- and γ-Bi2 O3 are confirmed by the XRD and PL spectroscopy. The optical transmission spectra indicated narrower band gap of α-/β-/γ-Bi2 O3 nanocomposites. The photocatalytic performance of the samples studied by degradation of methyl orange (MeO) and compared based on multi-heterojunction formation . The composite nanostructures exhibited about twice as high photocatalytic activity than single-phase nanostructures. Cyclic photocatalytic degradation reveal stable performance of α-/β-/γ-Bi2 O3 nanocomposites for the long term and cyclic utilisation. The enhanced photocatalytic activity can be attribute to the formation of heterojunctions between α-, β- and γ-Bi2 O3 . . In addition, PL spectra indicated that the recombination rate of samples after thermal treatment are much lower than that of samples before thermal treatment.